(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article explores the role of HR analytics in the strategic management of enterprises within the digital economy. The importance of data-driven management models in enhancing human capital efficiency is analyzed. The study develops scientific and practical recommendations for integrating HR metrics into strategic decision-making and optimizing personnel policy through predictive analytics.